2017
DOI: 10.1186/s13045-017-0400-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic value of disruptor of telomeric silencing-1-like (DOT1L) expression in patients with ovarian cancer

Abstract: BackgroundEpigenetics has been known to play a critical role in regulating the malignant phenotype. This study was designed to examine the expression of DOT1L (histone 3 lysine 79 methyltransferase) and H3K79 methylation in normal ovarian tissues and ovarian tumors and to explore the function of DOT1L and its underline mechanisms in ovarian cancer.MethodsThe expression of DOT1L and H3K79 methylation in 250 ovarian tumor samples and 24 normal ovarian samples was assessed by immunohistochemistry. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…This indicates that sst1 activation may inhibit cell proliferation via negative regulation of PI3K/AKT pathway, which is a common mechanism that has been previously reported with other components of the SST system . In line with this concept, treatment with this sst1 agonist also inhibited CCND3 expression, which has been previously linked with proliferation promotion and is modulated by AKT phosphorylation, which could suggest a novel mechanism of action for BIM‐23926 sst1 agonists in PCa (ie, sst1/pAKT/CCND3). On the other hand, the effect exerted by this sst1 agonist on 22Rv1 cells does not seem to be mediated by the promotion of apoptosis since p53 mRNA expression levels were not altered by this treatment; however, further studies would be necessary before a clear conclusion can be reached in this regard.…”
Section: Discussionsupporting
confidence: 78%
“…This indicates that sst1 activation may inhibit cell proliferation via negative regulation of PI3K/AKT pathway, which is a common mechanism that has been previously reported with other components of the SST system . In line with this concept, treatment with this sst1 agonist also inhibited CCND3 expression, which has been previously linked with proliferation promotion and is modulated by AKT phosphorylation, which could suggest a novel mechanism of action for BIM‐23926 sst1 agonists in PCa (ie, sst1/pAKT/CCND3). On the other hand, the effect exerted by this sst1 agonist on 22Rv1 cells does not seem to be mediated by the promotion of apoptosis since p53 mRNA expression levels were not altered by this treatment; however, further studies would be necessary before a clear conclusion can be reached in this regard.…”
Section: Discussionsupporting
confidence: 78%
“…Dot1 and its mammalian homolog, Dot1L, possess histone methyltranferase activity toward histone H3K79 , which regulates diverse cellular processes such as transcriptional regulation, cell cycle regulation, DNA damage response, differentiation, and development of leukemia . Recently, several publications have reported that Dot1L plays a crucial role in leukemia as well as in solid tumors, such as breast cancer, esophageal squamous cell carcinoma, colorectal cancer, prostate cancer, gastric cancer, and ovarian cancer . Furthermore, Dot1L is a drug target for mixed‐lineage leukemia (MLL) gene‐rearranged leukemia .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Dot1L is a drug target for mixed‐lineage leukemia (MLL) gene‐rearranged leukemia . Several Dot1L inhibitors have shown effective suppression of proliferation, migration, and invasion in ovarian cancer and breast cancer . However, in the current literature, the role of Dot1L on OSCC tumorigenesis and progression has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the vital functioning of DOT1L in the mixed lineage leukemia (MLL)-rearranged leukemia has been shown [8], and thus DOT1L-targeted inhibitors have been used in rearranged leukemia [9]. In solid tumors, DOT1L is also involved in its progression, such as breast cancer [10], ovarian cancer [11], and lung cancer [12]. However, to date, the therapeutic value and the prognostic impact of DOT1L in GC has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%